2010
DOI: 10.1186/1471-2334-10-285
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different sampling techniques and of different culture methods for detection of group B streptococcus carriage in pregnant women

Abstract: BackgroundStreptococcus agalactiae (group B streptococcus; GBS) is a significant cause of perinatal and neonatal infections worldwide. To detect GBS colonization in pregnant women, the CDC recommends isolation of the bacterium from vaginal and anorectal swab samples by growth in a selective enrichment medium, such as Lim broth (Todd-Hewitt broth supplemented with selective antibiotics), followed by subculture on sheep blood agar. However, this procedure may require 48 h to complete. We compared different sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
96
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 40 publications
14
96
0
2
Order By: Relevance
“…Studies investigating GBS in vaginal samples alone detected prevalence rates ranging between 11% and 19.8%, whereas recto-vaginal cultures reveal higher colonization rates, varying between 22% and 29.5% 8,[23][24][25] . In this study, the GBS isolation rates increased by 18.4% and 20.5% for the culture and PCR methods, respectively, when perianal samples were included in the analysis.…”
Section: Tablementioning
confidence: 99%
“…Studies investigating GBS in vaginal samples alone detected prevalence rates ranging between 11% and 19.8%, whereas recto-vaginal cultures reveal higher colonization rates, varying between 22% and 29.5% 8,[23][24][25] . In this study, the GBS isolation rates increased by 18.4% and 20.5% for the culture and PCR methods, respectively, when perianal samples were included in the analysis.…”
Section: Tablementioning
confidence: 99%
“…Cultures performed in the early third trimester have a relatively low predictive value in identifying women colonized at term [5]. Collection of samples from both the lower vagina and rectum through the anal sphincter provides significantly higher yield than does collection of vaginal samples alone [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Several culture-based studies have reported higher carriage rates of GBS in the rectum than in the vagina [18,26,27], supporting the idea that the gastrointestinal tract is the reservoir for vaginal GBS. Meyn et al [28] showed that rectal colonization with GBS was the most significant predictor of vaginal colonization, suggesting that the vagina becomes colonized with GBS as a result of transfer of the organism from the rectum to the vagina.…”
Section: Introductionmentioning
confidence: 74%
“…Differences in colonization rates can also be attributed to variation in the culture and detection methods employed, including the media selected and collection sites used [17][18][19]. The aim of this study was to quantify group B streptococci in the vagina and rectum and to determine whether GBS loads in both sites corresponded, as an indication of the rectum as a reservoir of vaginal GBS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation